2015
DOI: 10.18632/oncotarget.6295
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer effect of bee venom on colon cancer cell growth by activation of death receptors and inhibition of nuclear factor kappa B

Abstract: Bee venom (BV) has been used as a traditional medicine to treat arthritis, rheumatism, back pain, cancerous tumors, and skin diseases. However, the effects of BV on the colon cancer and their action mechanisms have not been reported yet. We used cell viability assay and soft agar colony formation assay for testing cell viability, electro mobility shift assay for detecting DNA binding activity of nuclear factor kappa B (NF-κB) and Western blotting assay for detection of apoptosis regulatory proteins. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 43 publications
(47 reference statements)
2
46
0
2
Order By: Relevance
“…Further, BV administration to nude mice implanted with PC-3 cells resulted in inhibition of tumor growth and activity of NF-κB accompanied with apoptotic cell death [42]. Similar effects on BV were observed in colon cancer cells where activation of death receptors and inhibition of nuclear factor kappa B were observed to be regulating the cancer death [51]. The study demonstrated that BV inhibited growth of colon cancer cells through induction of apoptosis without any effect on FHC colon epithelial normal cells.…”
Section: Anticancer Effects Of Bv and Its-conjugatesmentioning
confidence: 97%
See 1 more Smart Citation
“…Further, BV administration to nude mice implanted with PC-3 cells resulted in inhibition of tumor growth and activity of NF-κB accompanied with apoptotic cell death [42]. Similar effects on BV were observed in colon cancer cells where activation of death receptors and inhibition of nuclear factor kappa B were observed to be regulating the cancer death [51]. The study demonstrated that BV inhibited growth of colon cancer cells through induction of apoptosis without any effect on FHC colon epithelial normal cells.…”
Section: Anticancer Effects Of Bv and Its-conjugatesmentioning
confidence: 97%
“…Further, the DNA binding activity of nuclear factor kappa B (NF-κB) was also inhibited by BV treatment. In addition, BV significantly suppressed tumor growth in vivo [51]. …”
Section: Anticancer Effects Of Bv and Its-conjugatesmentioning
confidence: 99%
“…TUNEL ( Figure 1C) and DNA laddering ( Figure 1D) assays results showed that BV induced DNA fragmentation in cells, so it is indeed, the antiproliferative activity of BV involves induction of apoptosis. Although the apoptotic potential of BV has been previously documented (27), the effect on the near normal cells was unclear. Overall, our results suggest that BV displays its pharmacological effects via induction of apoptotic pathway rather than necrosis.…”
Section: Discussionmentioning
confidence: 97%
“…Bee venom (BV) has anticancer activity and is a traditional medicine for treating skin diseases, cancerous tumors and rheumatism. Recently, Zhenget al have evidence that BV can induce apoptosis by activating DR4 and DR5 and inhibiting NF-kB, thereby inhibiting the growth of colon cancer cells [124].…”
Section: Other Therapiesmentioning
confidence: 99%
“…People with colon cancer are the result of many factors interacting with obesity, sedentary, diet, alcohol, smoking, low-fi ber intake, high-fat diet, sleep, and lack of exercise are all related to the incidence of colon cancer [133][134][135][136]. Colon cancer can be prevented to a large extent.…”
Section: Preventionmentioning
confidence: 99%